Linear forward and backward locomotion for amphibious vehicle with rocker bogie mechanism - Hasnal, Muhammad Hakimi; Toha @ Tohara, Siti Fauziah; Antong, Hasmawati; Muhammad Samuri, Suzani; Mohd Nor, Elya; Mohd Khairuddin, Ismail (Persatuan Saintis Muslim Malaysia, 2024)
Amphibious vehicles, capable of operating on both land and water, are essential for applications such as search and rescue, environmental monitoring, and military operations. This study investigates the linear forward and backward locomotion of an amphibious vehicle using advance simulation tools. A detailed 3D model from SolidWorks was integrated into MATLAB's Simulink and Simscape to simulate and analyze the vehicle's motion dynamics. The simulation results demonstrated efficient and stable linear locomotion, with effective control mechanisms ensuring smooth and controlled movement where the peak motor current of 1.8A during start-up was reduced to a steady-state current of 0.8A, and power dissipation decreased from 0.25W to 0.1W, indicating significant energy efficiency. These findings validate the robustness of the design and highlight areas for potential optimization. future work will focus on further refining the vehicle's design and conducting real-world testing to validate and enhance its performance.